Analysis of Consumer Attitudes, Purchasing Patterns, and Consumption Patterns in Choosing Broiler Chicken and/or Local Chicken in Natar District, South Lampung Regency - Navarina Ajeng Pratiwi; Firdasari Firdasari; Adia Nugraha (International Journal of Economic and Business Research, 2026)
This empirical study examines the structural interplay among consumer attitudes, purchasing patterns, and domestic consumption trajectories in selecting broiler and local chicken within Natar District, South Lampung Regency. Utilizing a cross sectional survey design with sixty household food decision makers selected via accidental sampling at traditional and modern retail hubs, primary behavioral datasets were collected and evaluated through the Multiattribute Fishbein model alongside descriptive statistical processing. The empirical results demonstrate that consumer attitudes toward both poultry variants fall into the moderately favorable category, with total attitude scores reaching 120.99 for broiler chicken and 121.68 for local chicken. Broiler chicken exhibits superior performance in economic accessibility, market availability, and muscle fiber tenderness, while local chicken is favored for taste authenticity, nutrient density, and health safety. Purchasing and consumption patterns indicate a balanced reliance on traditional and modern market channels, with broiler chicken functioning as the dominant weekly protein staple owing to intensive regional supply trajectories, short preparation cycles, and clear sensory preferences for fried thigh and breast cuts.